Donors With Previous Malignancy: When Is It Safe to Proceed With Organ Transplantation? - Vitor Turra; Joao Manzi; Sarah Rombach; Simone Zaragoza; Raphaella Ferreira; Giselle Guerra; Kendra Conzen; Trevor Nydam; Alan Livingstone; Rodrigo Vianna; Phillipe Abreu (Transplant International)
The growing number of organ donors in the United States, from 14,011 in 2012 to 21,374 in 2022, highlights progress in addressing the critical issue of organ shortages. However, the demand remains high, with 17 patients dying daily while on the waiting list. As of August 2023, over 103,544 individuals are awaiting transplants, predominantly for kidneys (85.7%). To expand the donor pool, the inclusion of elderly donors, including those with a history of malignancies, is increasingly considered. In 2022, 7% of all donors were aged 65 and above, despite the complexities their medical histories may introduce, particularly the risk of donor-transmitted cancer (DTC). This review examines the challenges and potential benefits of using donors with known malignancy histories, balancing the risks of DTC against the urgency for transplants. A critical analysis is presented on current knowledge and the decision-making processes that consider cancer types, stages, and patient survival outcomes. The goal is to identify missed opportunities and improve strategies for safe and effective organ transplantation from this donor demographic.